Physical demands of refereeing rugby sevens matches at different competitive levels - Sant'Anna, R. T.; Roberts, S. P.; Moore, L. J.; Stokes, K. A. (The Journal of Strength and Conditioning Research, 2021)
The aim of this study was to compare the physical demands of officiating across different competitive levels in rugby sevens. An observational design was used involving 27 referees (26 men and 1 woman, age: 27 ± 6 years, body mass [mean ± SD]: 78.5 ± 9.3 kg, and height: 179 ± 5 cm). Global Navigation Satellite Systems data were collected across a total of 114 matches during 5 separate rugby sevens tournaments played in England—between May and July 2018—categorized into 4 competitive levels: (a) international, (b) professional, (c) semiprofessional, and (d) amateur. Compared with referees officiating at the international, professional, and semiprofessional levels, referees officiating at the amateur level covered less total (p < 0.001) and relative distance (p < 0.001). In addition, these referees covered more distance walking and jogging (p < 0.001). Amateur referees also completed fewer sprints (p = 0.006), repeated high-intensity efforts (RHIEs) per game (p < 0.001), and spent longer between RHIEs (p = 0.015). Finally, for the amateur referees, the duration of the longest repeated high-intensity bout (i.e., worst case scenario) was lower (p < 0.001), with less distance covered (p < 0.001) and fewer high-intensity accelerations (p < 0.001). Refereeing rugby sevens is therefore more physically demanding at higher competitive levels, particularly in terms of high-intensity efforts. The results provide vital information for practitioners involved in the physical preparation of rugby sevens referees.